Determination of pore size distributions using the Dual Site-Bond Model: Experimental evidence - López, Raúl Horacio (2002)
In previous papers, we have described a suitable method to obtain pore size distributions for voids and necks using the Dual Site-Bond Model (DSBM) and Monte Carlo simulations. This method basically consists in the determination of the corresponding size distributions by using adsorption-desorption hysteresis data. Void size frequency functions are featured from the ascending curve. From the descending curve, we obtain a characteristic pressure value that will give us, via a quasi-universal curve, information about the neck size distribution function. In this work, we use our method to predict, using experimental hysteresis loops, the size distributions of several mesoporous samples. Once these functions are determined, we simulate the adsorption-desorption isotherms on a simple cubic network of voids and necks whose radii are sampled from the obtained size distributions. Comparison with experimental data is performed, drawing out fruitful conclusions and future perspectives based on the simplicity and predictive capability of the method.